Analisis Self Efficacy Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share - Mulia Suryani; Welly Apria (Rumah Jurnal IAIN Bukittinggi, 2021)
Self-efficacy of students in class XI TSM B SMK Negeri 1 Bukit Sundi is still low so it has a negative impact on self-efficacy and student mathematics learning outcomes. The purpose of this study was to determine how students' self efficacy after applying Think pair square type cooperative learning models. This type of research is a descriptive method with a qualitative approach. The research subjects were all students of class XI TSM SMK Negeri 1 Bukit Sundi, amounting to two classes. The sampling technique is purposive sampling. The class chosen as the sample class is XI TSM B. To obtain the research data, an instrument in the form of a self efficacy questionnaire was used to interpret the self efficacy scores. The results obtained were 20% for the very strong criteria and 80% for the strong criteria, with an average of all indicators being 64.53% including the strong criteria. Dare to face the challenges is at the highest percentage with a percentage of 67.36% which is included in the strong criteria. He was sure that his success would be at the lowest percentage with the percentage of 60.19% and included in the strong criteria. It can be concluded that the students' self-efficacy during the application of Think pair square type cooperative learning models in class XI TSM B SMK Negeri 1 Bukit Sundi Solok Regency with strong criteria on each indicator and needed continuous and continuous development Self efficacy siswa di kelas XI TSM B SMK Negeri 1 Bukit Sundi masih rendah sehingga berakibat terhadap hasil belajar matematika siswa. Tujuan penelitian ini adalah untuk mengetahui bagaimanakah self efficacy siswa setelah menerapkan model pembelajaran kooperatif tipe Think pair Square. Jenis penelitian adalah penelitian dekriptif kualitatif. Subjek penelitian adalah siswa kelas XI TSM B. Untuk memperoleh data penelitian digunakan instrumen berupa angket self efficacy dengan cara menginterpretasikan skor self efficacy. Hasil persentase rata-rata seluruh indikator adalah 64,53% termasuk pada kriteria kuat. Indikator Berani menghadapi tantangan berada pada persentase tertinggi dengan jumlah persentase sebesar 67,36% yang termasuk pada kriteria kuat. Yakin akan keberhasilan dirinya berada pada persentase terendah dengan jumlah persentase yaitu 60,19% dan termasuk pada kriteria kuat. Dapat disimpulkan bahwa Self efficacy siswa selama penerapan model pembelajaran kooperatif tipe Think pair square di kelas XI TSM B SMK Negeri 1 Bukit Sundi Kabupaten Solok dengan kriteria kuat pada masing-masing indikator dan diperlukan pengembangan secara terus menerus dan berkelanjutan.